Peran Pilihan Pendekatan Pemecahan Masalah dan Karakteristik Risiko Dalam Mengatasi Gangguan pada Risiko Rantai Pasokan - Dhevi Dadi Kusumaningtyas; Ketut Purwantoro (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
The purpose of this study is to examine the constraints that arise in supply chain activities by considering the influence of risk characteristics on the choice of problem solving approach taken by management. There are 524 consumers who use goods delivery services in the Central Java region. This study was built based on the initial assumption that risks with high and low magnitude (High Risk Magnitude and Low Risk Magnitude) trigger network mobilization between actors, risk monitoring, communication between business actors and delivery service providers, resources and facilities so that it influences the choice of a solution approach. problems in supply chain management. We assume that risk with high strength has a positive effect on the choice of problem solving that provides a win-win solution. Conversely, risk with a low probability has a negative effect on the choice of mutually beneficial problem solving solutions. Our final findings through statistical tests conclude that the influence of risk attributes on the choice of problem solving approach is fully facilitated by timely assistance and collaborative problem solving.